Galanin and Neuropeptide Y Interaction Enhances Proliferation of Granule Precursor Cells and Expression of Neuroprotective Factors in the Rat Hippocampus with Consequent Augmented Spatial Memory - Mirchandani-Duque, Marina; Barbancho-Fernández, Miguel Ángel; López-Salas, Alexander; Álvarez-Contino, José Erik; García-Casares, Natalia; Fuxe, Kjell; Borroto Escuela, Dasiel Óscar; Narváez-Peláez, Manuel (IOAP-MPDI, 2022)
Dysregulation of hippocampal neurogenesis is linked to several neurodegenereative diseases, where boosting hippocampal neurogenesis in these patients emerges as a potential therapeutic approach. Accumulating evidence for a neuropeptide Y (NPY) and galanin (GAL) interaction was shown in various limbic system regions at molecular-, cellular-, and behavioral-specific levels. The purpose of the current work was to evaluate the role of the NPY and GAL interaction in the neurogenic actions on the dorsal hippocampus. We studied the Y1R agonist and GAL effects on: hippocampal cell proliferation through the proliferating cell nuclear antigen (PCNA), the expression of neuroprotective and anti-apoptotic factors, and the survival of neurons and neurite outgrowth on hippocampal neuronal cells. The functional outcome was evaluated in the object-in-place task. We demonstrated that the Y1R agonist and GAL promote cell proliferation and the induction of neuroprotective factors. These effects were mediated by the interaction of NPYY1 (Y1R) and GAL2 (GALR2) receptors, which mediate the increased survival and neurites’ outgrowth observed on neuronal hippocampal cells. These cellular effects are linked to the improved spatial-memory effects after the Y1R agonist and GAL co-injection at 24 h in the object-in-place task. Our results suggest the development of heterobivalent agonist pharmacophores, targeting Y1R–GALR2 heterocomplexes, therefore acting on the neuronal precursor cells of the DG in the dorsal hippocampus for the novel therapy of neurodegenerative cognitive-affecting diseases
Keywords: Neurobiología del desarrollo; Neuropeptide Y1 receptor; Galanin 2 receptor; Receptor–receptor interaction; Neurogenesis; Dorsal hippocampus; Neuroprotection; BDNF; Bcl-2; Neurodegenerative diseases; Spatial memory